The Economic Value of Flexibility when there is Disagreement - Arnoud W.A. Boot; Anjan V. Thakor (Tinbergen Institute, 2003)
We develop an economic theory of “flexibility”, which we interpret as the discretion orability to make a decision that others disagree with. We show that flexibility is essentiallyan option for the decisionmaker, and can be valued as such. The value of the flexibilityoption is decreasing in the extent to which the decisionmaker's future decision-relevantopinion is correlated with the opinions of others who may be able to impede the decision.We argue that flexibility drives economic decisions in a significant way. Theapplications we consider are: the entrepreneur's choice of flexibility in the initial mix offinancing raised, the use of flexibility to understand differences in security design and thefirm's security-issuance decision, the impact of flexibility on the use of collateral inlending, the role of flexibility in capital budgeting decisions, the effect of flexibilityconsiderations in the design of contracts in a principal-agent setting, the interpretation of“power” and conformity in organizations in the context of flexibility, and the choice betweenprivate an public ownership in the context of flexibility.
Keywords: D83; G30; G32; 330; Managerial Decision Making; Corporate Finance.; Entscheidung; Fremdkapital; Theorie; Flexibilität